Optical film and display device including the same

By dispersing fibrous nanowires in the light-transmitting matrix of the optical film, improving the stability and arrangement characteristics of the polymer chain, the problem that the optical film is difficult to meet both mechanical and optical properties is solved, and excellent mechanical and optical properties are achieved.

CN119585650APending Publication Date: 2025-03-07KOLON INDUSTRIES INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380054659.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-17
Filing Date
2023-07-18
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

When the existing optical film replaces glass as a display device to cover the window, it is difficult to meet excellent mechanical and optical properties at the same time.

Method used

By dispersing fibrous or filamentous nanowires in the light-transmitting matrix, the stability and arrangement characteristics of the polymer chain are improved, thereby improving the mechanical strength and optical properties of the optical film.

Benefits of technology

The excellent mechanical and optical properties of the optical film are achieved, making it suitable as a cover window for display devices, and has good elongation, recovery and light transmittance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119585650A_ABST
    Figure CN119585650A_ABST
Patent Text Reader

Abstract

One embodiment of the present invention provides an optical film and a display device comprising the same, the optical film comprising: a light-transmitting matrix comprising a polymer resin; and nanowires dispersed in the light transmissive matrix, wherein: the polymer resin comprises at least one of an imide repeating unit and an amide repeating unit; the nanowire comprises microcrystals; and the crystallites are linear.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an optical film and a display device including the same, and more particularly, to an optical film having excellent mechanical properties. Background Art

[0002] Recently, for the purpose of reducing the thickness and weight of a display device and increasing its flexibility, it has been considered to use an optical film instead of glass as a cover window of a display device. In order for the optical film to be used as a cover window of a display device, the optical film needs to have excellent optical properties and excellent mechanical properties. For example, the optical film needs to have properties such as excellent strength, hardness, wear resistance, and flexibility.

[0003] Nanowires may be added as fillers to impart desired physical properties to optical films requiring various physical properties. The nanowires may vary depending on the physical properties required of the optical film. Summary of the invention

[0004] Technical issues

[0005] Therefore, the present disclosure has been made in view of the above problems, and one aspect of the present disclosure is to provide an optical film including fiber-shaped or filament-shaped nanowires dispersed in a light-transmitting matrix.

[0006] Another aspect of the present disclosure is to provide an optical film comprising fibrous or filamentary nanowires dispersed in a light-transmitting matrix, wherein the fibrous or filamentary nanowires entangle polymer chains constituting the light-transmitting matrix to improve stability and alignment characteristics of the polymer chains.

[0007] Another aspect of the present disclosure is to provide an optical film including fibrous or filamentous nanowires dispersed in a light-transmitting matrix to provide excellent elongation and recovery.

[0008] Yet another aspect of the present disclosure is to provide a display device including the optical film.

[0009] Technical Solution

[0010] According to one aspect of the present disclosure, an optical film is provided, comprising: a light-transmitting matrix comprising a polymer resin; and nanowires dispersed in the light-transmitting matrix, wherein the polymer resin comprises at least one of an imide repeating unit and an amide repeating unit, the nanowires comprise crystallites, wherein the crystallites are linear, and the optical film has at least one of the structures represented by Formula 1, Formula 2, and Formula 3 below.

[0011] [Formula 1]

[0012]

[0013] [Formula 2]

[0014]

[0015] [Formula 3]

[0016]

[0017] Wherein, n is in the range of 50 to 10,000, m is in the range of 50 to 10,000, and p is in the range of 100 to 20,000.

[0018] According to another aspect of the present disclosure, a display device is provided, including a display panel and an optical film disposed on the display panel.

[0019] Beneficial Effects

[0020] According to one embodiment of the present disclosure, the nanowires included in the optical film have a fiber or filament shape and can entangle the polymer chains constituting the light-transmitting matrix, thereby improving the mechanical strength of the optical film.

[0021] According to one embodiment of the present disclosure, an optical film including fibrous nanowires may have excellent mechanical properties and excellent optical properties. The optical film according to one embodiment of the present disclosure has excellent optical and mechanical properties and is thus used as a cover window of a display device. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is a schematic diagram showing an optical film according to one embodiment of the present disclosure.

[0023] Figure 2 is a cross-sectional view showing a portion of a display device according to another exemplary embodiment of the present disclosure.

[0024] Figure 3 It is shown Figure 2 An enlarged cross-sectional view of portion “P” in FIG. DETAILED DESCRIPTION

[0025] Hereinafter, embodiments of the present disclosure will be described in detail with reference to the accompanying drawings. However, the following embodiments are only exemplarily provided for clear understanding of the present disclosure and do not limit the scope of the present disclosure.

[0026] The shapes, sizes, proportions, angles and numbers disclosed in the drawings for describing the embodiments of the present disclosure are examples only, and the present disclosure is not limited to the details shown. Throughout the specification, the same reference numerals refer to the same elements. In the following description, when the detailed description of the relevant known functions or configurations is determined to be unnecessary to obscure the main points of the present disclosure, the detailed description will be omitted.

[0027] In the case where terms such as "include", "have" or "include" are used in this specification, other parts may also exist unless "only" is also used. Unless otherwise specified, terms in the singular form may include plural meanings. In addition, when explaining an element, even if there is no explicit description thereof, the element is understood to include a range of error.

[0028] When describing a positional relationship, for example, when “on,” “above,” “below,” or “next to” is used to describe the positional relationship, a case where there is no contact between them can be included unless “just” or “directly” is used.

[0029] Spatially related terms such as "under," "below," "lower," "above," and "upper" may be used herein to describe the relationship between one device or element and another device or element as shown in the figures. It will be understood that, in addition to the directions depicted in the figures, spatially related terms are intended to include different orientations of the device during use or operation of the device. For example, if the device in a figure is inverted, the elements described as being "under" or "below" other elements will be located "above" the other elements. Therefore, the exemplary terms "under" or "below" can include the meanings of both "under" and "above." In the same manner, the exemplary terms "above" or "upper" can include the meanings of both "above" and "under."

[0030] When describing a time relationship, for example, when "after", "subsequently", "next", or "before" is used to describe a time sequence, the case of a non-continuous relationship may be included unless "just" or "directly" is used.

[0031] It will be understood that although the terms "first", "second", etc. may be used herein to describe different elements, these elements are not limited by these terms. These terms are only used to distinguish one element from another element. Therefore, within the technical concept of the present disclosure, the first element may be referred to as the second element.

[0032] It should be understood that the term "at least one" includes all combinations related to one or more items. For example, "at least one of the first element, the second element, and the third element" can include all combinations of two or more elements selected from the first, second, and third elements, as well as the first, second, and third elements individually.

[0033] The features of the various embodiments of the present disclosure may be partially or completely combined or combined with each other, and may interact with each other in various ways and be driven technically. The embodiments of the present disclosure may be performed independently of each other, or may be performed together in a related manner.

[0034] Figure 1 is a schematic diagram showing an optical film 100 according to one embodiment of the present disclosure. According to one embodiment of the present disclosure, a film having light transmittance is referred to as an "optical film 100".

[0035] The optical film 100 according to one embodiment of the present disclosure includes: a light-transmitting matrix 110 ; and nanowires 120 dispersed in the light-transmitting matrix 110 .

[0036] The light-transmitting matrix 110 may be light-transmitting. According to one embodiment of the present disclosure, the light-transmitting matrix 110 may be flexible. For example, the optical film according to one embodiment of the present disclosure may be bendable, foldable, or rollable. Therefore, the optical film 100 according to one embodiment of the present disclosure may be light-transmitting and may be bendable, foldable, or rollable.

[0037] According to an embodiment of the present disclosure, the light-transmitting matrix 110 may include a polymer resin. The polymer resin included in the light-transmitting matrix 110 may include at least one of an imide repeating unit and an amide repeating unit.

[0038] The polymer resin according to one embodiment of the present disclosure may be prepared from a monomer component including a dianhydride and a diamine. Specifically, the polymer resin may include an imide repeating unit formed from a dianhydride and a diamine.

[0039] However, the polymer resin according to one embodiment of the present disclosure is not limited thereto, and the polymer resin may be prepared from a monomer component containing a dicarbonyl compound in addition to a dianhydride and a diamine. The polymer resin according to one embodiment of the present disclosure may have an imide repeating unit and an amide repeating unit. For example, the polymer resin having an imide repeating unit and an amide repeating unit may be a polyamide-imide resin.

[0040] According to one embodiment of the present disclosure, the polymer resin may include a polyimide-based polymer. Examples of polyimide-based polymers may include polyimide polymers, polyamide polymers, polyamide-imide polymers, and the like. According to one embodiment of the present disclosure, the polymer resin may be formed of, for example, a polyimide-based polymer resin.

[0041] The light-transmitting matrix 110 may have a thickness sufficient for the optical film 100 to protect the display panel. For example, the light-transmitting matrix 110 may have a thickness of 10 to 100 μm. The thickness of the light-transmitting matrix 110 may be the same as that of the optical film 100 .

[0042] The optical film 100 according to one embodiment of the present disclosure includes the nanowires 120. The optical characteristics of the optical film 100 may be improved by light scattering caused by the nanowires 120.

[0043] Hereinafter, the nanowire 120 included in the optical film 100 and the crystallites included in the nanowire 120 will be described in more detail.

[0044] According to one embodiment of the present disclosure, the nanowire 120 may include a crystallite. A crystallite is also referred to as a "grain" and refers to each of a plurality of fine crystal units constituting a single crystal. According to one embodiment of the present disclosure, the crystallite may include aluminum. More specifically, the crystallite may include aluminum, oxygen, and hydrogen.

[0045] For example, the crystallites included in the nanowire 120 may include aluminum oxide hydroxide-based crystallites. The aluminum oxide hydroxide-based material is, for example, boehmite, and the boehmite may be represented by γ-AlO(OH).

[0046] According to one embodiment of the present disclosure, the crystallite may be linear and have at least one of structures represented by Formula 1, Formula 2, and Formula 3 below.

[0047] [Formula 1]

[0048]

[0049] The unit structure represented in brackets ([ ]) in Formula 1 may be referred to as a unit crystal.

[0050] [Formula 2]

[0051]

[0052] The unit structure represented in brackets ([ ]) in Formula 2 may be referred to as a unit crystal.

[0053] [Formula 3]

[0054]

[0055] The unit structure represented in brackets ([ ]) in Formula 3 may be referred to as a unit crystal.

[0056] Here, n in Formula 1, m in Formula 2, and p in Formula 3 represent the number of repeating units. In order to obtain crystallites and nanowires 120 having appropriate lengths, n in Formula 1, m in Formula 2, and p in Formula 3 may be adjusted.

[0057] According to one embodiment of the present disclosure, n in Formula 1 is in the range of 50 to 10,000, m in Formula 2 is in the range of 50 to 10,000, and p in Formula 3 is in the range of 100 to 20,000. When n, m, and p are determined within these ranges, the nanowire 120 may have a length of about 200 nm to about 4,000 nm.

[0058] When n is less than 50, it is difficult for the crystallites to have a sufficient length. When the length of the crystallites is not large, it is difficult to obtain a nanowire 120 of sufficient length. Therefore, the function of the nanowire 120 to entangle (or connect, or connect) the polymer chains in the light-transmitting matrix 110 may not be fully obtained.

[0059] When n is greater than 10,000, the length of the crystallite may be too large. As a result, the length of the nanowire 120 may be too long, and the dispersibility of the nanowire 120 may be deteriorated. Therefore, aggregation of the nanowire 120 may occur within the light-transmitting matrix 110.

[0060] When m is less than 50, it is difficult to give the crystallite a sufficient length. When the length of the crystallite is not large, it is difficult to increase the length of the nanowire 120. Therefore, the function of the nanowire 120 to entangle the polymer chain in the light-transmitting matrix 110 may not be sufficiently obtained.

[0061] When m is greater than 10,000, the length of the crystallite may be too large. As a result, the length of the nanowire 120 may be too long, and the dispersibility of the nanowire 120 may be deteriorated. Therefore, aggregation of the nanowire 120 may occur within the light-transmitting matrix 110.

[0062] When p is less than 100, it is difficult to give the crystallite a sufficient length. When the length of the crystallite is not large, it is difficult to increase the length of the nanowire 120. Therefore, the function of the nanowire 120 to entangle the polymer chain in the light-transmitting matrix 110 may not be fully obtained.

[0063] When p is greater than 20,000, the length of the crystallite may be too large. As a result, the length of the nanowire 120 may be too long, and the dispersibility of the nanowire 120 may be deteriorated. Therefore, aggregation of the nanowire 120 may occur within the light-transmitting matrix 110.

[0064] More specifically, n in Formula 1 may be in the range of 2,000 to 8,000. Within this range, the nanowires 120 have a length of about 1,000 to 4,000 nm, thereby fully exerting the function of entanglement of polymer chains and having excellent dispersibility. Therefore, the optical film 100 having uniform optical properties may be manufactured.

[0065] m in Formula 2 may be in the range of 2,000 to 8,000. Within this range, the nanowires 120 have a length of about 1,000 to 4,000 nm, thereby fully exerting the function of entanglement of polymer chains and having excellent dispersibility. Therefore, the optical film 100 having uniform optical properties may be manufactured.

[0066] p in Formula 3 may be in the range of 4,000 to 16,000. Within this range, the nanowires 120 have a length of about 1,000 to 4,000 nm, thereby fully exerting the function of entanglement of polymer chains and having excellent dispersibility. Therefore, the optical film 100 having uniform optical properties may be manufactured.

[0067] When the structure of the crystallite is expanded for better understanding of the structure of the crystallite, the crystallite may be represented by any one of Formula 4, Formula 5, and Formula 6.

[0068] The crystallite of Formula 1 may be represented by, for example, the following Formula 4. The following Formula 4 corresponds to the structure of Formula 1 in which n is 5.

[0069] [Formula 4]

[0070]

[0071] The crystallite of Formula 2 may be represented by, for example, the following Formula 5. The following Formula 5 corresponds to the structure of Formula 2 in which m is 4.

[0072] [Formula 5]

[0073]

[0074] The crystallite of Formula 3 may be represented by, for example, the following Formula 6. The following Formula 6 corresponds to the structure of Formula 3 in which p is 3.

[0075] [Formula 6]

[0076]

[0077] In Formulae 4, 5 and 6, "*" represents a binding site.

[0078] According to an embodiment of the present disclosure, the nanowire 120 may have a laminate including at least two or more crystallites.

[0079] According to one embodiment of the present disclosure, a plurality of crystallites may be stacked in a radial direction to form a laminate. According to one embodiment of the present disclosure, a structure formed by stacking a plurality of crystallites in a radial direction is referred to as a "laminate."

[0080] According to one embodiment of the present disclosure, two or more crystallites in the laminate may be bonded by hydrogen bonding.

[0081] According to one embodiment of the present disclosure, a hydrogen bond may be formed through oxygen (O).

[0082] According to one embodiment of the present disclosure, for example, H of an -OH group bonded to an aluminum atom of one crystallite may be hydrogen-bonded with O (oxygen) bonded to an aluminum atom of another crystallite to form a laminate.

[0083] According to one embodiment of the present disclosure, the laminate may include 2 to 40 crystallites.

[0084] According to one embodiment of the present disclosure, 2 to 40 crystallites may be stacked. The stacked crystallites may be included in a laminate.

[0085] According to one embodiment of the present disclosure, when crystallites ranging from 2 to 40 are stacked and included in a laminate, the nanowire 120 having an appropriate diameter may be obtained.

[0086] When the crystallites are not stacked, the diameter of the nanowire 120 is too small, and thus the stability of the nanowire 120 may be deteriorated. When more than 40 crystallites are stacked, the diameter of the nanowire 120 is too large, and it may be difficult to give the nanowire 120 a fiber shape.

[0087] According to one embodiment of the present disclosure, the laminate may include at least one of structures represented by Formula 7, Formula 8, and Formula 9 below.

[0088] According to one embodiment of the present disclosure, when crystallites including a structure represented by Formula 4 are stacked, a laminate may include, for example, a structure represented by the following Formula 7.

[0089] [Formula 7]

[0090]

[0091] According to one embodiment of the present disclosure, when crystallites including a structure represented by Formula 5 are stacked, a laminate may include, for example, a structure represented by the following Formula 8.

[0092] [Formula 8]

[0093]

[0094] According to one embodiment of the present disclosure, when crystallites including a structure represented by Formula 6 are stacked, a laminate may include, for example, a structure represented by the following Formula 9.

[0095] [Formula 9]

[0096]

[0097] In Formula 7, Formula 8 and Formula 9, “*” represents a binding site, and the dotted line represents a hydrogen bond between crystallites.

[0098] According to one embodiment of the present disclosure, the nanowire 120 may have a fiber shape. For example, a fiber may refer to a material whose length is much longer than its diameter. A fiber may refer to a thin and long linear material. A fiber may refer to a material having a linear structure. A fiber may also refer to a long and bendable material.

[0099] According to one embodiment of the present disclosure, the nanowire 120 may have a fiber shape including at least one of crystallites represented by Formula 1, Formula 2, and Formula 3. According to one embodiment of the present disclosure, the length of the nanowire 120 may be more than twice the diameter.

[0100] According to one embodiment of the present disclosure, the nanowires 120 are arranged in parallel with the polymer resin contained in the light-transmitting matrix 110. For example, the nanowires 120 may be bonded to the main chain of the polymer resin through a secondary bond such as a hydrogen bond or a dipole moment-like bond, and may be arranged in parallel with the polymer resin in the main chain direction.

[0101] According to one embodiment of the present disclosure, the nanowires 120 may be used to entangle polymer chains of a polymer resin included in the light-transmitting matrix 110. Therefore, the stability and alignment characteristics of the polymer chains are improved, thereby improving the mechanical properties of the light-transmitting matrix 110 and also improving the optical film 100.

[0102] According to one embodiment of the present disclosure, when the diameter of the nanowire 120 is defined as “A” and the length of the nanowire 120 is defined as “B”, a ratio of B / A may be in the range of 10 to 500.

[0103] When the ratio (B / A) of the length to the diameter of the nanowire 120 is less than 10, the nanowire 120 is not long enough and thus cannot fully exert the function of entangling the polymer chains and the effect of improving the stability and arrangement characteristics of the polymer chains.

[0104] When the ratio (B / A) of the length to the diameter of the nanowires 120 is higher than 500, the nanowires 120 are too long, thereby causing deterioration of dispersibility and aggregation in the light-transmitting matrix 110. As a result, the optical film 100 may have reduced light transmittance, increased haze, and deteriorated optical properties. In addition, at a portion where the nanowires 120 are aggregated, the mechanical strength of the optical film 100 may be reduced, thereby causing deterioration of the mechanical properties of the optical film 100.

[0105] According to one embodiment of the present disclosure, the ratio (B / A) of the length to the diameter of the nanowire 120 may be, for example, in the range of 50 to 500. More specifically, the ratio (B / A) of the length to the diameter of the nanowire 120 may be, for example, in the range of 100 to 400, and may be in the range of 200 to 400. The ratio (B / A) of the length to the diameter of the nanowire 120 may be in the range of 300 to 400. According to one embodiment of the present disclosure, the nanowire 120 may have a diameter of 2 nm to 10 nm and a length of 200 nm to 4,000 nm.

[0106] According to one embodiment of the present disclosure, the diameter and length of the nanowire 120 may be measured by a transmission electron microscope (TEM).

[0107] When the diameter of the nanowire 120 is less than 2 nm, the stability of the nanowire 120 may be reduced, the nanowire 120 may be broken or fragmented, and thus the optical film 100 may be contaminated and the haze may increase. When the diameter of the nanowire 120 is greater than 10 nm, a portion of the nanowire 120 may protrude from the surface of the optical film 100, and the function of the nanowire 120 to entangle the polymer chain may be deteriorated.

[0108] When the length of the nanowire 120 is less than 200 nm, the function of the nanowire 120 to entangle the polymer chain may not be sufficiently obtained. When the length of the nanowire 120 exceeds 4,000 nm, the dispersibility of the nanowire 120 may be reduced, thereby causing the nanowire 120 to aggregate in the light-transmitting matrix 110.

[0109] According to one embodiment of the present disclosure, the length of the nanowire 120 can be controlled by the growth conditions of the nanowire 120 or the post-treatment of the nanowire 120. For example, the length of the nanowire 120 can be appropriately adjusted by temperature control during the growth of the nanowire 120. In addition, ultrasound or other energy can be applied to the nanowire 120 grown to a predetermined length so that the nanowire 120 can be cut into an appropriate length.

[0110] According to one embodiment of the present disclosure, the nanowire 120 may be surface-treated. For example, the nanowire 120 may be a fiber surface-treated with an organic compound having an alkoxy group.

[0111] According to one embodiment of the present disclosure, the content of the nanowire 120 may be in the range of 1 to 40 wt % with respect to the total weight of the optical film 100 .

[0112] When the content of the nanowires 120 is less than 1 weight % relative to the total weight of the optical film 100, the light transmittance of the optical film 100 may not be improved due to the insignificant light scattering effect of the nanowires 120, and the effect of improving the mechanical properties of the optical film 100 may not be significant because the function of the nanowires 120 to entangle the polymer chains is not fully achieved.

[0113] At the same time, when the content of the nanowires 120 is higher than 40 weight % based on the total weight of the optical film 100, the dispersibility of the nanowires 120 may be reduced, the haze of the optical film 100 may be reduced, and due to the excessive amount of the nanowires 120, aggregation of the nanowires 120 may occur, and the aggregated nanowires 120 may block light, thereby reducing the transmittance of the optical film 100.

[0114] More specifically, the content of the nanowires 120 may be adjusted to 3 to 40 wt %, 5 to 40 wt %, 5 to 30 wt %, or 5 to 20 wt % with respect to the total weight of the optical film 100 .

[0115] According to one embodiment of the present disclosure, the haze increase and the light transmittance reduction of the optical film 100 may be prevented, and the mechanical strength of the optical film 100 may be improved by controlling the diameter, length, and content of the nanowires 120 and improving the dispersion method.

[0116] According to one embodiment of the present disclosure, the optical film 100 may have a machine direction (MD) and a transverse direction (TD).

[0117] The direction in which the film is mechanically treated is called the "machine direction (MD)", and the direction perpendicular to the MD is called the "transverse direction (TD)". For example, when the film is stretched, the direction parallel to the stretching direction can be the machine direction (MD), when the film is cast, the direction parallel to the casting direction can be the machine direction (MD), and when the film is wound by a roll, the direction parallel to the winding direction can be the machine direction (MD).

[0118] According to one embodiment of the present disclosure, the machine direction (MD) is a direction parallel to the casting direction of the optical film 100 during the manufacturing process. The machine direction (MD) may also be referred to as the longitudinal direction. TD is a direction perpendicular to the MD. The transverse direction (TD) may also be referred to as the "width direction".

[0119] The optical film 100 according to one embodiment of the present disclosure may have an elongation of 5% to 40%.

[0120] According to one embodiment of the present disclosure, the elongation (%) of the optical film 100 may be obtained by measuring the elongation in MD and the elongation in TD according to ASTM D885 and then calculating their average value.

[0121] When the elongation (%) is less than 5%, the optical film 100 may not be suitable as a substrate or a protective layer of a foldable display. When the elongation (%) is higher than 40%, it may be difficult to recover due to excessive deformation.

[0122] The optical film 100 according to one embodiment of the present disclosure may have a recovery rate (nIT, %) of 66 or more based on a thickness of 50 μm.

[0123] According to one embodiment of the present disclosure, the recovery rate (nIT, %) of the optical film 100 may be obtained by calculating the degree of recovery of the optical film 100 after removing the optical film 100 pressed with a diamond quadrangular pyramid having an angle of 136° according to ISO 14577-1.

[0124] When the recovery rate (nIT) is less than 66, the recovery force of the optical film 100 is insufficient, and thus, creases or indentations may remain on the optical film 100 .

[0125] The optical film 100 according to one embodiment of the present disclosure may have an elastic modulus (EIT) of 3,800 MPa or more based on a thickness of 50 um.

[0126] According to one embodiment of the present disclosure, the elastic modulus (EIT, indentation modulus) of the optical film 100 is measured using a nanoindenter according to ISO14577-1 and 12mN / 12s / creep 5s / 24°C, 40RH%. The nanoindenter used in this specification is HM-2000 from Fischer.

[0127] According to one embodiment of the present disclosure, the optical film 100 may include the fibrous nanowires 120 and may have a high elastic modulus (EIT).

[0128] According to one embodiment of the present disclosure, the fibrous nanowires 120 entangle the polymer constituting the light-transmitting matrix 110 , particularly, polymer chains, so that the optical film 100 has an elongation of about 5% to 40% and a relatively large recovery rate (nIT) of 66 or more.

[0129] According to one embodiment of the present disclosure, the optical film 100 may have a yellowness index of 3 or less.

[0130] According to one embodiment of the present disclosure, even if the optical film 100 includes the nanowires 120 having a ratio (B / A) of length to diameter in the range of 10 to 500, the nanowires 120 are uniformly dispersed in the optical film 100 and have a degree of orientation in a certain range, so that the yellowness index of the optical film 100 does not increase greatly, and the optical properties do not deteriorate. More specifically, the optical film 100 may include the nanowires 120 having a ratio (B / A) of length to diameter in the range of 100 to 400. Even in this case, the yellowness index of the optical film 100 does not increase greatly, and the optical properties do not deteriorate.

[0131] According to one embodiment of the present disclosure, the optical film 100 may have a haze of 2% or less, and more specifically, may have a haze of 1% or less. Although the nanowires 120 included in the light-transmitting matrix 110 are relatively long, the diameter of the nanowires 120 is small, so that the increase in haze caused by the nanowires 120 can be prevented. In particular, although the fibrous nanowires 120 are used, by adjusting the diameter, length, length-to-diameter ratio (B / A) and content ratio of the nanowires 120 dispersed in the light-transmitting matrix 110, and improving the dispersibility of the nanowires 120, a haze of 2% or less, for example, a haze of 1% or less can be imparted to the optical film 100.

[0132] In addition, according to one embodiment of the present disclosure, the optical film 100 can have a light transmittance of 88% or more. Although the length of the nanowires 120 included in the light-transmitting matrix 110 is relatively long, the diameter of the nanowires 120 is small, so that the light transmittance reduction caused by the nanowires 120 can be prevented. In particular, although the fibrous nanowires 120 are used, by adjusting the diameter, length, length-to-diameter ratio (B / A) and content ratio of the nanowires 120 dispersed in the light-transmitting matrix 110, and improving the dispersibility of the nanowires 120, a light transmittance of 88% or more can be imparted to the optical film 100.

[0133] Figure 2 is a cross-sectional view showing a portion of a display device 200 according to another embodiment of the present disclosure, Figure 3 yes Figure 2 Enlarged cross-sectional view of "P" in FIG.

[0134] Reference Figure 2 , a display device 200 according to another embodiment of the present disclosure includes a display panel 501 and an optical film 100 on the display panel 501 .

[0135] Reference Figure 2 and Figure 3The display panel 501 includes: a substrate 510; a thin film transistor TFT on the substrate 510; and an organic light emitting device 570 connected to the thin film transistor TFT. The organic light emitting device 570 includes: a first electrode 571; an organic light emitting layer 572 on the first electrode 571; and a second electrode 573 on the organic light emitting layer 572. Figure 2 and Figure 3 The display device 200 shown in FIG. 2 is an organic light emitting display device.

[0136] The substrate 510 may be formed of glass or plastic. Specifically, the substrate 510 may be formed of plastic such as a polyimide-based resin or an optical film. Although not shown, a buffer layer may be provided on the substrate 510.

[0137] The thin film transistor TFT is disposed on the substrate 510. The thin film transistor TFT includes: a semiconductor layer 520; a gate electrode 530 insulated from the semiconductor layer 520 and at least partially overlapping the semiconductor layer 520; a source electrode 541 connected to the semiconductor layer 520; and a drain electrode 542 spaced apart from the source electrode 541 and connected to the semiconductor layer 520.

[0138] Reference Figure 3 , a gate insulating layer 535 is disposed between the gate electrode 530 and the semiconductor layer 520 . An interlayer insulating layer 551 may be disposed on the gate electrode 530 , and a source electrode 541 and a drain electrode 542 may be disposed on the interlayer insulating layer 551 .

[0139] A planarization layer 552 is disposed on the thin film transistor TFT to planarize the top of the thin film transistor TFT.

[0140] The first electrode 571 is disposed on the planarization layer 552. The first electrode 571 is connected to the thin film transistor TFT through a contact hole disposed in the planarization layer 552.

[0141] A bank layer 580 is disposed on the planarization layer 552 in a portion of the first electrode 571 to define a pixel region or a light emitting region. For example, the bank layer 580 is disposed at boundaries between a plurality of pixels in a matrix form to define respective pixel regions.

[0142] The organic light emitting layer 572 is disposed on the first electrode 571. The organic light emitting layer 572 may also be disposed on the bank layer 580. The organic light emitting layer 572 may include one light emitting layer, or two or more light emitting layers stacked in a vertical direction. The organic light emitting layer 572 may emit light having any one color of red, green, and blue, and may emit white light.

[0143] The second electrode 573 is disposed on the organic light emitting layer 572 .

[0144] The first electrode 571 , the organic light emitting layer 572 , and the second electrode 573 may be stacked to constitute the organic light emitting device 570 .

[0145] Although not shown, when the organic light emitting layer 572 emits white light, each pixel may include a color filter for filtering the white light emitted from the organic light emitting layer 572 based on a specific wavelength. The color filter is formed in a light path.

[0146] The thin film encapsulation layer 590 may be disposed on the second electrode 573. The thin film encapsulation layer 590 may include at least one organic layer and at least one inorganic layer, and the at least one organic layer and the at least one inorganic layer may be alternately disposed.

[0147] The optical film 100 is disposed on the display panel 501 having the above stacked structure. The optical film 100 includes a light-transmitting matrix 110 and nanowires 120 dispersed in the light-transmitting matrix 110.

[0148] Hereinafter, a method of manufacturing the optical film 100 according to another embodiment of the present disclosure will be described.

[0149] A method of manufacturing an optical film 100 according to one embodiment of the present disclosure includes: first dispersing nanowires 120 in a resin solution for forming a light-transmitting matrix 110 to prepare a first mixed solution; improving the arrangement characteristics of the nanowires 120 in the first mixed solution; and casting the first mixed solution to prepare a cast film.

[0150] According to one embodiment of the present disclosure, a polyimide-based resin solution may be used as a resin solution for forming the light-transmitting matrix 110 .

[0151] More specifically, a method for manufacturing an optical film 100 according to an embodiment of the present disclosure includes: preparing a polyimide resin powder; dissolving the polyimide resin powder in a first solvent to obtain a polyimide resin solution; dispersing the nanowires 120 in a second solvent to prepare a nanowire dispersion; and mixing the nanowire dispersion with the polyimide resin solution to prepare a first mixed solution.

[0152] DMAc (N, N-dimethylacetamide) can be used as the first solvent. DMAc (N, N-dimethylacetamide) or methyl ethyl ketone (MEK) can be used as the second solvent, but one embodiment of the present disclosure is not limited thereto, and other known solvents can be used as the first solvent and the second solvent.

[0153] The fibrous nanowires 120, for example, the fibrous nanowires 120 having a high aspect ratio have a large length compared to their diameter, and thus, may be easily aggregated or coagulated in the light-transmitting matrix 110. Therefore, the nanowires 120 need to have excellent dispersibility in the first mixed solution.

[0154] According to one embodiment of the present disclosure, in order to improve the dispersibility of the nanowire 120, for example, p-toluenesulfonic acid (PTSA) may be used as an additive, but one embodiment of the present disclosure is not limited thereto, and other known additives may be used to improve the dispersibility of the nanowire 120.

[0155] According to one embodiment of the present disclosure, the pH of the first mixed solution may be adjusted to improve the dispersibility of the nanowires 120. For example, the pH of the first mixed solution may be adjusted to a range of 5 to 7. Thus, aggregation or coagulation of the nanowires 120 may be prevented.

[0156] Next, the first mixed solution is cast, dried, and heat-treated to form the optical film 100. According to one embodiment of the present disclosure, the film formed by casting the first mixed solution may be referred to as a "cast film", and the film manufactured by drying and heat-treating the cast film may be referred to as an "optical film 100". The cast film may be referred to as an "uncured film".

[0157] In order to improve the orientation of the nanowires 120, casting may be performed by rod coating.

[0158] According to one embodiment of the present disclosure, the orientation direction and degree of the nanowires 120 may be changed by adjusting the pressure applied to the casting film formed by casting.

[0159] In addition, during drying and heat treatment of a cast film formed by casting, convection may be prevented so that the nanowires 120 may be oriented in a specific direction.

[0160] Specifically, when convection is generated in the casting film using heat drying, the orientation of the nanowires 120 may be reduced. Therefore, the casting film may be dried slowly to prevent convection. For example, the casting film may be dried while the temperature is increased from 80°C to 120°C at a rate of 1°C / 1 minute. When drying is performed to a certain extent, the orientation of the nanowires 120 may be fixed.

[0161] Hereinafter, the present disclosure will be described in more detail with reference to Preparation Examples and Examples. However, the following Preparation Examples and Examples should not be construed as limiting the scope of the present disclosure.

[0162] <Preparation Example 1: Preparation of polymer-imide polymer solid>

[0163] 776.655 g of N,N-dimethylacetamide (DMAc) was added to a 1 L reactor equipped with a stirrer, a nitrogen injector, a dropping funnel, a temperature controller and a cooler, and the reactor was purged with nitrogen. Then, the temperature of the reactor was adjusted to 25°C, 54.439 g (0.17 mol) of bis (trifluoromethyl) benzidine (TFDB) was dissolved therein, and the temperature of the solution was maintained at 25°C. 15.005 g (0.051 mol) of biphenyltetracarboxylic dianhydride (BPDA) was further added thereto and completely dissolved therein by stirring for 3 hours, and 22.657 g (0.051 mol) of 4,4′-(hexafluoroisopropylidene)phthalic anhydride (6FDA) was further added thereto and completely dissolved therein. The reactor temperature was lowered to 10°C, 13.805 g (0.068 mol) of terephthaloyl chloride (TPC) was further added thereto, and reacted at 25°C for 12 hours to obtain a polymer solution having a solid content of 12 wt%.

[0164] 17.75 g of pyridine and 22.92 g of acetic anhydride were added to the obtained polymer solution, stirred for 30 minutes, stirred again at 70° C. for 1 hour, and cooled to room temperature. 20 L of methanol was added to the obtained polymer solution to precipitate a solid, and the precipitated solid was filtered, pulverized, washed with 2 L of methanol, and vacuum dried at 100° C. for 6 hours to prepare a polyimide-based polymer solid as a powder. The prepared polyimide-based polymer solid is a polyamide-imide polymer solid.

[0165] <Example 1>

[0166] 850 g of DMAc (first solvent) was added to a 1 L reactor, and the reactor was stirred for a while while the temperature of the reactor was maintained at 10° C. Then, 127 g of the polyamide-imide (polyimide resin powder) prepared as a solid powder in Preparation Example 1 was added to the reactor, stirred for 1 hour, and heated to 25° C. to prepare a liquid polyimide resin solution.

[0167] Alumina fiber dispersion was used as a dispersion added to the nanowire 120. Specifically, nanowires 120 having an average particle diameter of about 4 nm and an average length of about 1,600 nm were used in a DMAc (N,N-dimethylacetamide, a second solvent) solution. As the nanowire 120, aluminum-based nanowires having a laminate structure represented by Formula 7 were used. The nanowires were used as a dispersion, and the content of the nanowires was 10 wt % based on the total weight of the solid content (polyimide-based resin component+nanowires).

[0168] Specifically, another 1L reactor was filled with the nanowire dispersion, the temperature of the reactor was maintained at 25°C, and the prepared liquid polyimide-based resin solution was slowly added thereto over 1 hour using a cylinder pump to obtain a first mixed solution containing the nanowire dispersion and the polyimide-based resin solution. Here, the nanowire 120 is an aluminum-based nanowire having a laminate structure represented by Formula 7.

[0169] When measured immediately after the first mixed solution is prepared, the pH of the first mixed solution is greater than 8. In order to improve the alignment characteristics of the nanowires 120, a weak acid such as acetic acid is added to the first mixed solution to adjust the pH of the first mixed solution to be within the range of 5 to 7. The first mixed solution thus prepared is a polyimide-based resin solution in which the fibrous nanowires 120 are dispersed.

[0170] The obtained first mixed solution is cast. A casting substrate is used for casting. At this time, there is no particular restriction on the type of the casting substrate. The casting substrate can be a glass substrate, a stainless steel (SUS) substrate, a Teflon substrate, etc. According to one embodiment of the present disclosure, a glass substrate is used as the casting substrate.

[0171] Specifically, the obtained first mixed solution was applied to a glass substrate and cast. In order to improve the orientation of the nanowires 120, the first mixed solution was applied to a glass substrate (casting substrate) and cast while applying a force of 30 N in a direction perpendicular to the glass substrate. As a result, a cast film was prepared.

[0172] Specifically, the cast film was prepared by slowly drying in a hot air oven at a rate of 1°C / min from 80°C to 120°C for about 40 minutes to maintain the orientation of the nanowires 120. Then, the fabricated film was peeled off from the glass substrate and fixed to a frame with pins.

[0173] The frame with the optical film fixed thereon was slowly heated from 100° C. to 280° C. in a vacuum oven over 2 hours, slowly cooled and separated from the frame to obtain an optical film. The optical film was heated again at 250° C. for 5 minutes.

[0174] As a result, the optical film 100 having a thickness of 50 μm, which includes the light-transmitting matrix 110 and the nanowires 120 dispersed in the light-transmitting matrix 110, is completed.

[0175] <Examples 2 to 33>

[0176] The optical film 100 was prepared under the conditions of Table 1 in the same manner as in Example 1, and is referred to as "Examples 2 to 33", respectively. In Table 1, "Formula 7" refers to an aluminum-based nanowire having a laminate structure represented by Formula 7. "Formula 8" refers to an aluminum-based nanowire having a laminate structure represented by Formula 8. "Formula 9" refers to an aluminum-based nanowire having a laminate structure represented by Formula 9.

[0177] <Comparative Examples 1 to 10>

[0178] Optical films 100 were prepared under the conditions of Table 1 in the same manner as in Example 1, and are respectively referred to as “Comparative Examples 1 to 10”.

[0179] [Table 1]

[0180]

[0181]

[0182] <Measurement Example>

[0183] The optical films prepared in Examples 1 to 33 and Comparative Examples 1 to 10 were subjected to the following measurements.

[0184] (1) Measurement of elongation (modulus)

[0185] The modulus of each of the optical films prepared according to Examples 1 to 33 and Comparative Examples 1 to 10 was measured using a universal tensile tester (MODEL 5967) of Instron Corporation in accordance with ASTM D885.

[0186] -Measurement standard within three hours after membrane manufacturing

[0187] - Load cell 30kN, clamp 250N.

[0188] - Sample size: 10mm x 100mm, tensile speed: 25mm / min

[0189] - Since orientation occurs in the coating direction, the coating direction is referred to as "MD" and the direction perpendicular to the coating is referred to as "TD", and the measurement is performed in both directions.

[0190] (2) Measurement of recovery rate (nIT)

[0191] According to one embodiment of the present disclosure, the recovery rate (nIT, %) of the optical film 100 can be obtained by calculating the degree of recovery of the optical film 100 according to ISO 14577-1 after removing the optical film 100 pressed with a diamond quadrangular pyramid having an angle of 136°. The recovery rates of each of the optical films prepared according to Examples 1 to 33 and Comparative Examples 1 to 10 were measured using HM-2000 of Fischer Measurement Technologies.

[0192] (3) Measurement of elastic modulus (EIT)

[0193] The elastic modulus (EIT, indentation modulus) of each optical film prepared according to Examples 1 to 33 and Comparative Examples 1 to 10 was measured using HM-2000 of Fischer Measurement Technologies according to ISO 14577-1 and 12 mN / 12 s / creep 5 s / 24° C., 40 RH % conditions.

[0194] (4) Measurement of yellowness index (YI.)

[0195] The yellowness index of each of the optical films prepared according to Examples 1 to 33 and Comparative Examples 1 to 10 was measured using a spectrophotometer (CM-3700D, KONICA MINOLTA) according to ASTM E313 standard.

[0196] (5) Haze measurement

[0197] The haze of each optical film prepared according to Examples 1 to 33 and Comparative Examples 1 to 10 is measured by cutting the optical film into specimens having a size of 50 mm x 50 mm, measuring the haze of each specimen 5 times according to ASTM D1003 using a haze meter, for example, a haze meter from Murakami Color Laboratories (model name: HM-150), and calculating the average of the five measured haze values.

[0198] (6) Measurement of light transmittance (%)

[0199] The average light transmittance of each of the optical films prepared according to Examples 1 to 33 and Comparative Examples 1 to 10 at a wavelength of 360 to 740 nm was measured using a spectrophotometer (CM-3700D, KONICA MINOLTA).

[0200] <Measurement Results>

[0201] The results of the measurements of physical properties are shown in Table 2 below.

[0202] [Table 2]

[0203]

[0204]

[0205] As can be seen from the measurement results of Table 2, the optical film 100 according to the embodiment of the present disclosure has excellent light transmittance, yellowness index, and haze, and thus has excellent optical properties.

[0206] Furthermore, it can be seen that the optical film 100 according to the embodiment of the present disclosure has excellent elongation and recovery rate, and excellent mechanical properties.

[0207] On the other hand, it can be seen that the optical film according to Comparative Example 1 does not include nanowires, and thus has poor mechanical properties, particularly low elastic modulus (EIT), compared with the optical film according to the embodiment.

[0208] It can be seen that the optical films according to Comparative Examples 2 to 4 include an excess amount of nanowires based on weight % and have deteriorated optical properties compared to the optical film according to the embodiment. In particular, it can be seen that the optical films according to Comparative Examples 2 to 4 have a higher yellowness index than the optical film according to the embodiment.

[0209] The optical films according to Comparative Examples 5 to 7 include short nanowires. In order to use a predetermined weight ratio, for example, 10 wt % of nanowires in the optical film, the optical films of Comparative Examples 5 to 7 should use relatively more nanowires than the optical film according to the embodiment. Since a relatively large amount of nanowires is used, it is considered that the optical films of Comparative Examples 5 to 7 have increased haze and increased yellowness.

[0210] The optical films according to Comparative Examples 8 to 10 included very long nanowires. As a result, it is considered that the optical films according to Comparative Examples 8 to 10 have low optical properties, specifically, high yellowness indexes.

[0211] [Explanation of Reference Numerals]

[0212] 100: Optical film

[0213] 110: light-transmitting matrix

[0214] 120: Nanowires

[0215] 200: Display device

[0216] 501: Display panel

Claims

1. An optical film comprising: a light-transmissive matrix comprising a polymer resin; and nanowires dispersed in the light-transmitting matrix, wherein the polymer resin comprises at least one of an imide repeating unit and an amide repeating unit, The nanowires comprise crystallites, Wherein, the microcrystals are linear, and the optical film has at least one of the structures represented by the following Formula 1, Formula 2, and Formula 3: [Formula 1] [Formula 2] [Formula 3] Where n is in the range of 5010,000, m is in the range of 50 to 10,000, p is in the range of 100 to 20,000.

2. The optical film according to claim 1, wherein The nanowire has a diameter of 2 nm to 10 nm and a length of 200 nm to 4,000 nm.

3. The optical film according to claim 1, wherein The nanowire has a laminate including at least two or more crystallites bonded together.

4. The optical film according to claim 3, wherein: The laminate comprises at least two or more crystallites, The crystallites are bonded by hydrogen bonds.

5. The optical film according to claim 3, wherein: The laminate includes 2 to 40 crystallites.

6. The optical film according to claim 3, wherein: The laminate includes at least one of the structures represented by the following Formula 7, Formula 8, and Formula 9: [Formula 7] [Formula 8] [Formula 9] 7. The optical film according to claim 1, wherein: The nanowires are present in an amount of 1 wt % to 40 wt % based on the total weight of the optical film.

8. The optical film according to claim 1, wherein: n is in the range of 2,000 to 8,000, m is in the range of 2,000 to 8,000, p ranges from 4,000 to 16,000.

9. The optical film according to claim 1, wherein: The optical film has an elongation of 5% to 40%.

10. The optical film according to claim 1, wherein The optical film has a recovery rate (nIT, %) of 66 or more based on a thickness of 50 μm.

11. The optical film according to claim 1, wherein: The yellowness index of the optical film is 3 or less.

12. The optical film according to claim 1, wherein: The optical film has a haze of 2% or less.

13. The optical film according to claim 1, wherein: The optical film has a light transmittance of more than 88%.

14. A display device, comprising: Display panel; and The optical film according to any one of claims 1 to 13 provided on the display panel.